The History of Articulators: ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œScribingÃƒÂ¢Ã¢â€šÂ¬Ã¢â€žÂ¢ÃƒÂ¢Ã¢â€šÂ¬Ã¢â€žÂ¢ ArticulatorsÃƒÂ¢Ã¢â€šÂ¬Ã¢â‚¬ÂThose with Functionally Generated Custom Guide Controls, Part III - Edgar N. Starcke, DDS (Journal of Prosthodontics, 2005)
THIS is the third article in a series on ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œScribingÃƒÂ¢Ã¢â€šÂ¬Ã‚Â articulators, or those with functionally generated custom guide controls.